Nurses' Perception of Evidence-Based Knowledge, Attitude and Practice: A Quantitative Study in Teaching Hospitals - Rohollah Kalhor; Mohammad Azmal; Omid Khosravizadeh; Saeideh moosavi; Maryam Sadat Asgari; Fatemeh Gharaghieh (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Providing healthcare services of the highest quality and quantity, based on the results of scientific research, is one of the main tasks of nurses. The aim of this study is to evaluate nurses’ perception of evidence-based knowledge, attitude and practice in selected hospitals of Iran. Methods: This study was a descriptive cross-sectional analysis that was conducted to investigate nurses’ perception of evidence-based practice (EBP). Two hundred-and-sixty nurses were selected randomly from six hospitals in Qazvin city in Iran to participate in the study. An evidence-based practice questionnaire was used to assess the dimensions of EBP. Descriptive and inferential statistics using frequency tables, t-student statistics, Pearson correlation coefficient and ANOVA were used for data analysis. Results: According to this study, nurses’ perception of EBP was generally above average (3.91 out of 7) and average of Practice, attitude and knowledge/skills were 4.14, 3.78 and 3.74 respectively. There was no statistically significant relationship among EBP dimensions and gender, age and job tenure (P-value > 0.05). There was a statistically significant relation between attitude of nurses and type of employment (P-value < 0.05). Conclusion: In this study, the mean of evidence-based practice among nurses was at a level higher than the average. The attitude of the nurses who were studied was moderate, but thanks to the low level of their knowledge about EBP, training programs based on needs assessments resulting from the findings of this study were suggested that could improve nurses’ knowledge of EBP.